Implikasi Hukum Penerbitan Covernote yang Tidak Sesuai Fakta Oleh Notaris dalam Perjanjian Kredit Refinancing PT Barito Riau Jaya - Megawati H.M. (Jurnal Hukum Lex Generalis, 2025)
This study discusses the problem when a notary makes a covernote that does not match the facts in a credit agreement at PT Barito Riau Jaya. Covernotes are often used by banks to disburse credit, but actually do not have legal force like a deed. When the contents of the covernote are incorrect, this can be detrimental to the state and violate the law. This study uses a normative legal approach and finds that notaries can be subject to administrative sanctions, even criminal and civil, if they make a misleading covernote.